2019
DOI: 10.1002/cphc.201900307
|View full text |Cite
|
Sign up to set email alerts
|

Strong Microheterogeneity in Novel Deep Eutectic Solvents

Abstract: With the increasing application of template assisted syntheses in deep eutectic solvents and successful application of hydrophobic deep eutectic solvents in extraction processes, where microheterogeneity plays a major role, suggestions for novel deep eutectic solvents which exhibit strong microheterogeneity are desirable. Therefore, classical molecular dynamics simulations were carried out on deep eutectic solvent systems constructed of choline chloride and some of its derivatives mixed with ethylene glycol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…Fluorescence and infrared spectroscopy studies demonstrated that changing the hydrocarbon chain length of both HBA and HBD affects the spatial and dynamic heterogeneity of the ionic DESs. [26][27][28] This view is in line with conclusions from WANS on alkylammonium bromide:glycerol DESs 29 and MD simulation of choline chloride derivatives:ethylene glycol DESs 30 that have related the microheterogeneous structure of DESs to the segregation of the apolar and polar groups of the cationic molecules into separated domains. The formation and the percolation of these domains are favored by larger chains, which reveal the role of the amphiphilic character of the cationic moieties.…”
Section: Introductionsupporting
confidence: 67%
“…Fluorescence and infrared spectroscopy studies demonstrated that changing the hydrocarbon chain length of both HBA and HBD affects the spatial and dynamic heterogeneity of the ionic DESs. [26][27][28] This view is in line with conclusions from WANS on alkylammonium bromide:glycerol DESs 29 and MD simulation of choline chloride derivatives:ethylene glycol DESs 30 that have related the microheterogeneous structure of DESs to the segregation of the apolar and polar groups of the cationic molecules into separated domains. The formation and the percolation of these domains are favored by larger chains, which reveal the role of the amphiphilic character of the cationic moieties.…”
Section: Introductionsupporting
confidence: 67%
“…Control of heterogeneity is an important task for the development of DESs for extraction and other separation applications [219,220]. Alizadeh et al [220] studied heterogeneity in DESs based on ChCl and its depravities with different lengths of the alkyl chain.…”
Section: Hydrophobic Deep Eutectic Solventsmentioning
confidence: 99%
“…They found that the cation chain length affects the density and transport properties of DESs. Alizadeh et al 39 Several simulation and experimental efforts have been conducted to investigate the interfacial properties of DESs. Most of these studies focus on the behavior of DES molecules near solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the cation chain length affects the density and transport properties of DESs. Alizadeh et al 39 investigated the microheterogeneity of DESs composed of choline chloride and its derivatives mixed with ethylene glycol using MD simulations. Their results show distinct polar and nonpolar parts in these DESs.…”
Section: Introductionmentioning
confidence: 99%